MRI to guide biopsies or avoid biopsies?. Issue 6 (November 2018) - Winoker, Jared S.; Pinto, Peter A.; Rastinehad, Ardeshir R.
Abstract : Purpose of review: To discuss contemporary data on the value of multiparametric MRI (mpMRI) for guiding the decision to biopsy men at risk for prostate cancer, as well as its utility in active surveillance programs. Recent findings: Although a systematic 12-core biopsy is the current standard of care for men with increased suspicion for prostate cancer, MRI with or without targeted biopsy has been shown to reliably improve the detection of clinically significant disease following a prior negative biopsy. At the same time, there is a growing body of evidence to support the use of MRI for diagnostic purposes in biopsy-naive patients, as well for enrolling and monitoring men on active surveillance programs. Summary: mpMRI is an evolving technology with great promise for altering our approach to prostate cancer diagnosis and surveillance. In conjunction with targeted biopsies, MRI offers greater specificity for the detection of clinically significant cancer and therefore may help to reduce overdetection of indolent disease while minimizing the risks and limitations of systematic biopsies.